2008
DOI: 10.1080/02841850802161023
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow edema: pathophysiology, differential diagnosis, and imaging

Abstract: Bone marrow edema (BME) has been a topic of increasing interest in the literature in recent years. BME is associated with numerous pathologies and is becoming recognized not only as a considerable pain generator, but also as an entity which is, in some cases, significantly linked to the worsening of patient prognosis. To date, no thorough imaging review of BME has been published. An electronic literature search was conducted through PubMed with a time parameter of January 1975 through December 2007. The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
0
14

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(143 citation statements)
references
References 99 publications
1
122
0
14
Order By: Relevance
“…1 Since then a wealth of publications have detailed the presence of BML in a wide variety of conditions ( Table 1). The presence of BML has been shown to be associated with pain and progression of disease in numerous studies, 2 and therefore various modalities have been tested as treatment options in the hope that they might reduce pain and progressions of disease. The purpose of this review is to summarise our current knowledge about the role of BMLs in inflammatory and non-inflammatory disease and the effects of current treatment regimens.…”
Section: Introductionmentioning
confidence: 99%
“…1 Since then a wealth of publications have detailed the presence of BML in a wide variety of conditions ( Table 1). The presence of BML has been shown to be associated with pain and progression of disease in numerous studies, 2 and therefore various modalities have been tested as treatment options in the hope that they might reduce pain and progressions of disease. The purpose of this review is to summarise our current knowledge about the role of BMLs in inflammatory and non-inflammatory disease and the effects of current treatment regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Uzun kemiklerde; önce epifiz ve apofiz, sonra diyafiz, en son olarak da sırasıyla distal ve proksimal metafizde yağlı konversiyon olur. Erişkin paternde kemik iliği 25 yaşına kadar tamamlanır ve kırmızı kemik iliği sadece aksiyel iskelette, sternumda, kotlarda, humerus ve femur metafizlerinde görülür [1][2][3].…”
Section: Kırmızı Kemik İliği Rekonversiyonuunclassified
“…Yağ baskılı T2A ve STIR'da ödem ve hemorajiye bağlı artmış sinyal izlenir (Resim 3A). T1A'da genellikle orta sinyalli belirsiz sınırlı heterojen subkortikal retiküler çizgilenmeler izlenir [3,6] (Resim 3B). Fakat travma mekanizmasına bağlı olarak subkondral alandan daha uzak yerleşimli de olabilir [6].…”
Section: Kontüzyonunclassified
See 1 more Smart Citation
“…44,45 In humans, ''bone marrow edema'' has been observed in a broad spectrum of local and multisystemic conditions, including degenerative, inflammatory, infectious, endocrine, metabolic, and neoplastic processes, and it is associated with increased pain, a more rapid progression, or a worsening prognosis. 48 Moreover, bone remodeling with associated bone marrow inflammation, neovascularization, stromal cell activation, and edema was observed histologically in an archived set of acute and chronically laminitic equine feet, providing the impetus for the current study. 13 Although the remodeling changes described in laminitic feet suggested that a direct correlation might exist between lamellar epidermal/dermal lesions and DP lesions in equine laminitis, the stepwise progression and extent of laminitis-associated DP pathology had not been thoroughly characterized or systematically quantified.…”
mentioning
confidence: 99%